Assessing the risk of estragole consumption from natural products in the Malaysian market by using the margin of exposure approach - M. Pauzi, Nur Azra; Arif, Akmal; Mirad, Razali; Aziz, Mohd Yusmaidie; Abdullah, Rozaini (Faculty of Medicine and Health Science, Universiti Putra Malaysia, 2023)
Introduction: Estragole is a naturally-occurring phytochemical found in variety of herbs, and spices, commonly used as food ingredients and in various natural products too. Despite some studies suggesting that estragole has health benefits, animal studies have shown that estragole is a hepatotoxic and genotoxic carcinogen, mainly due to the formation of its metabolites, specifically 1-hydroxyestragole. Objective: This study aims to perform health risk assessment of estragole in natural products from Malaysia by using the margin of exposure (MOE) approach. Methods: 30 samples of natural product were obtained from Malaysian market using targeted sampling strategy. All of the samples were extracted using methanol extraction and analyzed using Ultra Performance Liquid Chromatography (UPLC). The estimated daily intake (EDI) was calculated by using the quantified estragole concentrations and the recommended daily intake as stated on the product label. To assess the risk associated with estragole, the MOE approach was employed. Results: 9 out of 30 samples were found to contain estragole with levels ranging from 55.03 to 418.02 ¼g/g. The EDI values of estragole in these samples ranged from 0.99 - 9.44 ¼g/kg bw/day. Using the MOE approach, all positive samples were found to have MOE values less than 10,000 for long-term consumption, indicating high priority for risk management. However, for shorter-than-lifetime scenarios, the MOE values were above 10,000, indicating low priority for risk management. Conclusion: The presence of estragole in Malaysian natural products may raise health concern, especially when it is consumed daily over extended period.